2001
DOI: 10.1016/s0550-3213(01)00496-5
|View full text |Cite
|
Sign up to set email alerts
|

Gauge corrections and FI-term in 5D KK theories

Abstract: In the context of a five dimensional N=1 Kaluza Klein model compactified on S 1 /Z 2 × Z 2 we compute the one-loop gauge corrections to the self energy of the (zero-mode) scalar field. The result is quadratically divergent due to the appearance of a Fayet-Iliopoulos term.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
152
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(153 citation statements)
references
References 19 publications
1
152
0
Order By: Relevance
“…Dimensional analysis tells us that the naive divergence of these diagrams will be at most linear ͑and not quadratic͒, as expected for a boundary operator or, in other words, the sum over KK modes is convergent. This is clear in the massless limit where, if n 1 ϩn 2 ϩn 3 is odd, only 8 What is actually relevant is the relative sign between the mass and ⌫ 5 . Indeed, in five dimensions there are two inequivalent representations for ⌫ 5 which differ by a sign.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dimensional analysis tells us that the naive divergence of these diagrams will be at most linear ͑and not quadratic͒, as expected for a boundary operator or, in other words, the sum over KK modes is convergent. This is clear in the massless limit where, if n 1 ϩn 2 ϩn 3 is odd, only 8 What is actually relevant is the relative sign between the mass and ⌫ 5 . Indeed, in five dimensions there are two inequivalent representations for ⌫ 5 which differ by a sign.…”
Section: Discussionmentioning
confidence: 99%
“…This means that only a fermion with positive mass can play the role of a PV regulator. 8 Now that we have shown the basic formulas, we introduce the first regulator, which consists of replacing the fermion kinetic term in Eq. ͑A1͒ with "i‫ץ‬ " ϪM ͑ y ͒…→"i‫ץ‬ " ϪM ͑ y ͒…e ⑀"i‫ץ‬ " ϩM (y)…"i‫ץ‬ " ϪM (y)… , ͑A6͒…”
Section: Discussionmentioning
confidence: 99%
“…The same happens for the alternative model [24] where gauge multiplets and SU(2) L singlets live and the bulk and SU(2) L doublets are localized on the brane. This problem is however avoided in models with a single Higgs hypermultiplet, as those based on S 1 /Z 2 × Z 2 [25], although these models develop a Fayet-Iliopoulos quadratic divergence [26].…”
Section: Radiative Determination Of Supersymmetry Breakingmentioning
confidence: 99%
“…Before the compactification of the 5 Some authors [14,18] have found cuadratically divergent corrections with similar calculations, which suggests that this kind of computation is not very well established. There is also a quadratically divergent Fayet-Iliopoulos term in supersymmetric theories on orbifolds [15]. 6 In [4] a Poisson resummation is done before the proper time integral.…”
Section: Discussionmentioning
confidence: 99%